Impact of COVID-19 on Lifestyle and Nutritional Habits: A Gender-Based Analysis of Indonesian Students - Dewanti, Lintang Purwara; Sitoayu, Laras; Mardiyah, Sarah; Melani, Vitria (PT FORMOSA CENDEKIA GLOBAL, 2024)
The COVID-19 pandemic, originating from Wuhan, China, in December 2019 and declared a pandemic by WHO in March 2020, has led to significant global health impacts. This study explores the gender-specific effects of the pandemic on eating habits, stress levels, and weight changes among university students in Indonesia. This research conducted is a quantitative cross-sectional study. Data was collected online from 686 Indonesian university students over a 35-day period using a validated and reliable questionnaire. The questionnaire covered demographic information, eating habits, lifestyle factors, and weight changes. Univariate and bivariate analyses were performed to assess the differences between male and female students. A significant gender difference was observed in breakfast habits, with males more likely to eat breakfast regularly (p = 0.001). Stress levels were generally moderate, but females showed a higher tendency for severe stress compared to males, who exhibited more mild stress (p = 0.000). Both genders reported increased food consumption and decreased snacking frequency. No significant gender differences were found in supplement intake. Female students experienced higher stress levels and different eating habits compared to males. Educational institutions should promote awareness of healthy eating and stress management, particularly during crises like the COVID-19 pandemic